QAS 2022
DOI: 10.47750/qas/23.189.35
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty-Based Sustainable Competitive Advantage and Intention to Choose Back at One Bank

Abstract: The existence of banking institutions has an important role in the country's economy. Banking institutions have three main functions, namely financial intermediary, agent of development and agent of trust. The existence and sustainability of banking institutions must be pursued as much as possible by bank managers, because their existence can improve the economy. One of the efforts made by banking institutions is to channel credit to those in need to meet customer needs and to earn profits for banking institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Almost half of the more recent banking studies identify service quality as a main variable when investigating loyalty and found the higher the service quality, the more loyal customers will be (Lau et al. , 2013; Lee and Moghavvemi, 2015; Ngo Vu and Nguyen Huan, 2016; Bapat, 2017; Adi et al. , 2022; Özkan et al.…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…Almost half of the more recent banking studies identify service quality as a main variable when investigating loyalty and found the higher the service quality, the more loyal customers will be (Lau et al. , 2013; Lee and Moghavvemi, 2015; Ngo Vu and Nguyen Huan, 2016; Bapat, 2017; Adi et al. , 2022; Özkan et al.…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%